Maxillofacial prosthesis materials selection: Pemilihan bahan prostesis maksilofasial - Hastinawaty; Vinsensia Launardo (Makassar Dental Journal PDGI Makassar, 2024)
Maxillofacial prosthetic materials are used to replace parts of the face that are missing due to infection, disease and trauma. Ap-pearance and some functions can be restored with maxillofacial prostheses and improve the patient's quality of life. To achieve these functions, material selection is an important aspect of treatment planning. The literature review discusses the materials that can be used to make maxillofacial prostheses and how to select them by reviewing textbooks, clinical studies and articles from electronic databases Pubmed, Wiley, Google Schoolar with some keywords. The most common materials currently used for ma-nufacturing intraoral and extraoral prostheses are polymers and exhibit almost all the desired physical, biological and clinical properties although to date, none of the commercially available materials fulfil all the requirements of an ideal material. It is con-cluded that current maxillofacial prosthesis materials do not fully fulfil the required needs. There are advantages and disadvan-tages of certain materials so continued innovation to obtain new materials and further research needs to be done.